The Aim Of Islamic Education In Forming Insan Kamil From Ahmad Tafsir’s Perspective - Rahmadani Akbar; Afrida; Rahmad Alkhadafi (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2025)
The objectives of Islamic education are critical and require comprehensive study to ensure an effective learning process. Without a clear and detailed discussion of these objectives, various problems can arise, leading to deviations in the education system. An education system that does not have clear objectives tends to lose direction and fail to achieve the expected results, thus harming students and society. Ahmad Tafsir is one of the leading education figures in Indonesia. His ideas on education are widely contained in his works, which are important references in the development of Islamic education in Indonesia. This study uses a qualitative approach based on library research. The purpose of this study is to determine and analyze Ahmad Tafsir's thoughts on the objectives of Islamic education to form perfect humans. The results of this study indicate that Islamic education aims to develop good and noble human resources. Ahmad Tafsir said, that to create perfect humans according to the objectives of Islamic education, it is necessary to pay attention to three criteria for perfect humans, namely healthy and strong bodies, intelligent and clever thoughts, and high-quality spirituality.